O processo adaptativo de mulheres ao diabetes na perspectiva da teoria de Callista Roy - PASTANA, Elizama Nascimento (2020)
Diabetes mellitus represents a considerable economic burden for the individual and society, especially when poorly controlled, and most of the direct costs of its treatment are related to its complications, which compromise the productivity, quality of life and survival of individuals, which can often be reduced, delayed or avoided. The adaptive process to diagnosis is related to several factors, including adherence to the new lifestyle and drug treatment. The objective of this paper is to know the adaptive process of women to diabetes based on Callista Roy's theory. The methodology consists in an exploratory descriptive study of qualitative character. The study population consisted of women diagnosed with diabetes registered and attended at the Hypertension and Diabetes Program (HIPERDIA), at the Basic Health Unit of Guamá/Belém/Pará, the data collection occurred from January to June 2019. After collection, data were organized into 11 categories distributed in the four adaptive modes of Roy's theory. Through the content analysis of the categories it was found that most women showed concern about food and demonstrated a favorable adaptive process to the demands of the pathology, however, some pointed out difficulties in changing diet due to cultural and social factors and lack of knowledge about the nutritional value of food. Women presented favorable adaptation to drug treatment. Regarding the practice of physical activity, women develop activities regularly and understand the importance of this practice to disease control. All women interviewed had eyesight changes, but these were compromised with care related to diabetic retinopathy. The participants were active in relation to self-care with the skin. Regarding to living with family and society, most report that they can cope with the demands of the disease and establish their social relationships, they also highlighted the importance of interaction with health professionals for the positive impact on pathology adaptation and treatment follow-up. In this scenario, know the adaptive process of women to diabetes, as well as the changes experienced by this public is substantial so that nursing can establish appropriate care, considering the needs and interests of women, thus assisting in the process of adaptation to the diabetes demands and provide a positive impact on health and quality of life.